Les termitières, un univers de chasse (nord du Cameroun) - Christian Seignobos (Revue d'ethnoécologie)
Digging and smoking animals out of their holes have never been considered valuable hunting techniques in Northern Cameroonian communities, either Muslim or other. They are used by adult farmers using the surrounding areas of their plots.Among them, termite mounds’ hunters – namely here, the Gizigas from the Maroua region – remain a separate category associating knowledge about living termite mounds exploited once a year, during sexually matured winged adults’ swarming, and knowledge about dead termite mounds that have been given up by their colonies and become the refuge of a diverse, furry, priclkly and scaly animals. The hunters thus need to know many details about the ethology and “sociology” of the termite mounds’ roommates.The constant decrease of game, on the piedmonts of Mounts Mandara as well as in the adjacent Damaré plains, is making this formerly marginal hunting territory one of the rare ones that is still attractive today.